Biomechanical Characteristics on the Lower Extremity of Three Typical Yoga Manoeuvres - Elizabeth Whissell; Lin Wang; Pan Li; Jing Xian Li; Zhen Wei (Applied Bionics and Biomechanics)
This study was aimed at exploring the biomechanical characteristics of the lower extremity amongst three typical yoga manoeuvres. A total of thirteen experienced female yoga practitioners were recruited in the current study; they were all certified with the Yoga Alliance. A three-dimensional motion capture system with 10 cameras combined with four synchronised force plates was used to collect kinematics of the lower extremity and ground reactive force whilst the participants performed the crescent lunge pose, warrior II pose, and triangle pose. One-way repeated ANOVA was used in exploring the differences amongst the three yoga movements, and the significance was set to alpha<0.05. The triangle pose performed the largest range of motion (ROM) of the hip (90.5°±22.9°), knee (68.8°±23.1°), and ankle (46.4°±11.3°) in the sagittal plane and the hip (54.8°±6.5°), knee (42.4°±12.8°), and ankle (4.8°±1.7°) in the frontal plane amongst the three manoeuvres (P<0.05). No significant difference was found for the hip and ankle joint moment amongst the three manoeuvres (P>0.05). Knee joint travelled into 9.5° of extension and slight adduction of 1.94° whilst expressing the largest knee joint adduction moments (0.30±0.22 Nm/kg) in the triangle pose. The distribution of the angular impulse of the lower limb joints indicated that the hip joint contributed significantly the most in the sagittal and frontal planes of the three yoga manoeuvres (P<0.05), ranging from 51.67% to 70.56%. Results indicated that triangle pose may be superior to the other two manoeuvres, which improved hip joint ROM, strength, and dynamic stability. However, knee injuries such as osteoarthritis (OA) should be considered because of the large knee extensor angle and adductor moments.